Can Payroll Tax Cuts Help Firms during Recessions? - Youssef Benzarti; Jarkko Harju (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper estimates the effect of payroll tax cuts on firm-level employment and balance-sheet outcomes during economic downturns. We use two regional payroll tax cuts in Finland as well as the onset of the Great Recession to estimate the effect of the recession on firms treated by the payroll tax cuts compared to a similar control group. When implemented, prior to the Great Recession, we estimate that the payroll tax cuts had limited effects on employment and balance-sheet outcomes of firms located in the treated regions. However, when the recession starts, some of its negative effects were substantially hampered by the previously enacted payroll tax cuts in treated firms. These employment effects are exacerbated for men and low-skilled employees. We also find that sales and profits in treated firms respond differently in treated firms during the recession. We provide some evidence showing that firms that are liquidity con-strained are the ones that exhibit the strongest response. This shows that payroll tax cuts can make firms more resilient during downturns, possibly by relaxing liquidity constraints.
Keywords: H20; H22; H23; 330; labor costs; place-based policies; great recession; payroll taxes; employment; wages; firms; fiscal multipliers